Impact of traffic management alternatives on intersection capacity: Kahramanmaras - Öztürk, Gökçen (Hasan Kalyoncu Üniversitesi Fen Bilimleri Enstitüsü İnşaat Mühendisliği Ana Bilim Dalı, 2017)
The capacity of existing roads of city centers remains insufficient due to the increasing of population and correspondingly increasing the number of vehicles in our cities. For this reason, the mentality of 'Traffic Management becomes crucial to operating an optimum level capacity of a network of existing roads in our cities. Traffic Management that contains planning, control, and control implementations is an interdisciplinary topic to use a more efficiently network of roads in cities.It will be investigated impacts of environmental like emissions and noises which are due to enhancing the capacity of existing signalized intersection by using the developed software that is for traffic flow and intersection design and simulation.The capacity of intersections will be executed to simulate by VISSIM with 5 diffirent alternatives. These alternatives will have been evaulated according to where intersection is by VISSIM that is a simulation program. One of these alternatives was implemented by KMM (Kahramanmaraş Metropolitan Municipal) on the site, after that this alternative was compared between simulation results and new traffic counts that was renewed with new geometricric design. According to these results, the new geometric design with the simulation is 93% compatible.This project will been anticipated to be guiding for especially administrator. Especially, positive effects of the alternatives will be seen and assisted healtier investment before any high cost investments like a underpass, interchange etc will not be constructed in points that is insuffient capacity.

Kentlerimizdeki nüfus artışı ve dolayısıyla araç sahipliliği artışı kent merkezlerinde mevcut olan yolların kapasitelerinin yetersiz kalmasına sebep olmaktadır. Trafik yönetimi; kentlerdeki mevcut yol ağının daha verimli bir şekilde kullanılması için yapılan planlama, kontrol ve uygulamaları içermekte olan disiplinler arası bir konudur.Bu proje ilede, trafik akımı ve kavşak dizaynı simülasyonu için geliştirilmiş olan yazılımlar kullanılarak mevcut kavşak kapasitelerindeki artış ve bu kapasite artışının emisyonlar ve gürültü gibi çevresel etkileri incelenecektir. Kavşaklardaki kapasite artışı 5 farklı geometrik tasarımla simule edilecektir. Bu alternatifler kavşağın bulunduğu bölgeye uygun olarak VISSIM Ssimulasyon Pprogramı ile değerlendirilmiştir.ve her sinyalize kavşak için en yüksek kapasite artışını sağlayan alternatif bulunmuştur. Bu alternatiflerden Kahramanmaraş Büyükşehir Belediyesi tarafından arazide uygulanmış ve yeni geometrik düzenleme ilede kavşak sayımları yapılmıştır.Simulasyon sonuçları ile yeni geometrik düzenlemeden sonraki kavşak sayımları sonuçlarıyla %93 uyumlu olduğu hesaplanmıştır. Elde edilen bulgular, özellikle karar vericilere, kentlerimizde hangi projeleri uygulamaları gerektiği konusunda yol gösterici olmuştur.
Keywords: intersection capacity; geometric design; traffic management; emissions; delay times VISSIM